2019
DOI: 10.32098/mltj.04.2014.06
|View full text |Cite
|
Sign up to set email alerts
|

Tendon transfer for irreparable rotator cuff tears: indications and surgical rationale

Abstract: Background: treatment of symptomatic irreparable rotator cuff tears is extremely challenging because, at present, there are no ideal solutions to this problem. Many patients respond favorably to nonsurgical treatment. However, when conservative measures fail to improve the patient's pain and disability, surgery should be considered. Methods: different surgical techniques are available and the choice of the most appropriate procedure depends on the presenting symptoms, age of the patient, functional demand, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…O ur case was classified as a massive irreparable RCT based on the definition described above [1][2][3][4] . Previous clinical reports have documented that repair of this kind of RCT should involve the restoration of both cuff and capsule anatomy to maximize clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O ur case was classified as a massive irreparable RCT based on the definition described above [1][2][3][4] . Previous clinical reports have documented that repair of this kind of RCT should involve the restoration of both cuff and capsule anatomy to maximize clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…M assive rotator cuff tears (RCT) have been historically considered tears with a diameter ≥5 cm and/or that are involved in the detachment of at least two entire tendons 1,2 . An irreparable RCT is defined as a tear is unable to be reapproximated to its insertion on the tuberosities despite application of conventional release techniques, due to the degeneration, retraction, and fatty infiltration of cuff tissue 3,4 . A recent systematic review identified that 42% of RCT can be classified as irreparable tears 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of a massive irreparable posterosuperior rotator cuff tear, the force couples are often imbalanced and patients present with not only lack of function, but also significant pain and debility [ 14 ]. A lower trapezius tendon transfer in this setting aims to primarily relieve pain, but also to provide strength and function.…”
Section: Indicationsmentioning
confidence: 99%
“…Although reverse total shoulder arthroplasty results in effective pain relief, this option is often reserved for patients with degenerative changes and a less active lifestyle [ 17 ]. Tendon transfer surgery has become a more accepted treatment option for irreparable rotator cuff tears in patients desiring greater postoperative function, particularly strength and range of motion [ 8 , 10 , 13 , 14 ]. Specifically, the lower trapezius tendon transfer with Achilles tendon allograft augmentation is indicated for massive irreparable posterosuperior rotator cuff tears in patients with limited degenerative changes as well as in patients with paralytic shoulders following nerve injuries.…”
mentioning
confidence: 99%
“…The management of large and massive RoCTs in shoulders with minimal arthritis remains a dilemma for shoulder surgeons [15,16] . There are many options available, including specialised rehabilitation, simple arthroscopic surgery including debridement [17][18][19][20], long head of biceps tenotomy, bursectomy [21,22], various tendon transfers [23,24] through to formal repair of the tendon. This may be in the form of partial repair or complete repair where achievable.…”
Section: Introductionmentioning
confidence: 99%